L'analyse de cernes: applications aux études de croissance de quelques essences en peuplements naturels de forét dense africaine - Detienne, P.; Oyono, F.; Durrieu de Madron, L.; Demarquez, B.; Nasi, Robert (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 1998)
Knowledge of wood production, and particularly of diameter increment of trees, is central to forest management. This is one of the parameters contributing to determination of the length of the felling cycle as well as the maximum allowable cut without impoverishment of forest stands. Two techniques can be used to assess diameter increment of trees: analysis of growth rings and periodical measurements of circumference over a given period. The results obtained with several designs, in which trees have been periodically measured for more than ten years (Mopi, Irobo and La Téné in Cote de Ivoire, Mbaiki in Central African Republic and Oyane in Gabon), provide increments for each species. In the same way, several growth ring counts were carried out for species with visible annual growth rings, especially in Cameroon, Central African Republic and Gabon. This report describes the methodology used for growth ring analysis, the application of such analysis for each tree species, as well as a synthesis of the results obtained for the main species exploited in Central and West Africa. The following species are included: Ayous/Samba (Triplochiton sideroxylon), Sapelli (Entandrophragma cylindricum), Limba/Fraké (Terminalia superba), Sipo (Entandrophragma utile), Tali (Erythrophleum ivorense), Tiama (Entandrophragma angolensis), Kosipo (Entandrophragma candollei), Okoumé (Aucoumea klaineana) and Moabi (Baillonella toxisperma). It appears that the mean diameter increment of Meliaceae (Sapelli, Sipo, Kosipo and Tiama - Entandrophragma spp.) and Iroko (Milicia excelsa) is 4-5 mm/year. The increment is 2-3 mm/year for slow-growing species, such as Bossé clair (Guarea cedrata) and Kotibé (Nesogordonia papaverifera), while mean annual increment of Okoumé (Aucoumea klaineana) is slightly under 10 mm/year for trees with diameters from 20 to 100 cm.